Total Dissolved Gas Pressure Measurements for Assessing Contaminant Degradation Processes in Groundwater. Issue 1 (19th January 2017) - Roy, James W.; McLeod, Heather C.; Suchy, Martin; Smith, James E.
Abstract: The total dissolved gas pressure (PTDG ) probe has been used in groundwater studies for over a decade, but rarely in assessing contaminant degradation, despite the many degradation reactions that produce or consume dissolved gases. Here we present three studies to demonstrate the application of PTDG measurements to groundwater experiencing contaminant degradation, with discussion of its benefits and limitations. The first study is a pilot‐scale laboratory experiment simulating dissolved ethanol contamination of an anaerobic sand aquifer. Continuous monitoring of PTDG showed the rapid onset of microbial hydrocarbon degradation via denitrification and fermentation. The subsequent formation of a gas phase was revealed when PTDG began mimicking the bubbling pressure (PG *; sum of hydrostatic and atmospheric pressure), fluctuating with atmospheric pressure. Some deviations of PTDG above PG * occurred also, which may hold promise for signalling substantial changes in the rate or type of degradation process (here, the onset of methanogenesis). In the second study, synoptic field measurements at a petroleum plume site demonstrated how elevated PTDG could identify wells with evidence of hydrocarbon degradation (denitrification and/or methanogenesis). And finally, combined field measurements of dissolved oxygen (DO) and PTDG in monitoring wells of a nitrate‐contaminated aquifer (Abbottsford‐Sumas) revealed areas where denitrification was likely occurring. Limitations to PTDG use identified in these studies included the masking of degradation processes by the presence of a gas phase, as when trapped following water table fluctuations or formed from rigorous degradation reactions, and confounded assessment of PTDG patterns from other natural or anthropogenic processes that can also influence groundwater PTDG .